Two-Phases QR Authentication Algorithm (2PQRA) for Digital Energy and IoT Applications - Al-Ghaili A.M.; Kasim H.; Omar R.; Al-Hada N.M.; Hassan Z.; Hussain T.J.; Othman M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Automation; Codes (symbols); Cryptography; Internet of things; Authentication algorithm; Energy; Internet-based medias; Private information; Quick response code; Quick response code code; Security level; Simple++; Smart homes; Two phase; Authentication